Data for the industrial and municipal environmental wastes hazard contaminants assessment with integration of RES2D techniques and Oasis Montaj software - Arifin, M.H. (Elsevier Inc., 2020)
Industrial, and municipal wastes are part of the main sources of environmental hazards as well as groundwater and surface water pollutions. If not well composed, treated, and safely disposed, it could permeate through the subsurface lithologies by reaching down to the underground water aquifers, particularly in zones of unprotected aquifer units. Pollutants, most especially the landfills leachates that encompassed organic contaminants, ammonia, nitrates, total nitrogen, suspended solids, heavy metals and soluble inorganic salts, i.e., soluble nitrogen, sulphur compound, sulphate and chlorides, could posed undesirable environmental impacts due to inappropriate disposals that may give rise to gaseous fumes and leachate formations. An electrical resistivity geophysical technique utilizing the RES2D no-invasive, cost-effective and rapid method of data collection was integrated with the 3D Oasis Montaj software to approximate the volume of the generated rectangular prism model of the contaminants delineated from mixtures of the industrial, and municipal wastes plumes to be 312,000 m 3. Â© 2020 The Author(s)